Kepekaan Pastoral dalam Liturgi: Menuju Ibadah yang Berwajah Pastoral - Besly Yermy Tungaoly Messakh (†) (STFT Jakarta, Indonesia, 2020)
Through this paper, I elaborate the liturgical conversation from the perspective of pastoral theology. I argued that the whole liturgical practice was pastoral practice. Referring to the events of Christ, liturgical practice as pastoral practice is able to reform and transform the people in worship. I also argued that the planning and organizing of the liturgy should deliberately and take into account the pastoral dimension.